2002
DOI: 10.1146/annurev.astro.40.060401.093901
|View full text |Cite
|
Sign up to set email alerts
|

A Generalist Looks Back

Abstract: I have stayed at Cornell ever since, and I have essentially had only a single job in my whole life, but have switched fields quite often. I worked in nuclear astrophysics and in late-stellar evolution, estimated the Initial Mass Function for star formation and the metal enrichment of the interstellar medium. I suggested black hole accretion as the energy source for quasars, worked on molecule formation on dust grain surfaces, and was involved in 21-cm studies of gas clouds and disk galaxies. I collaborated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…The four have told their own versions of the story (Hoyle 1982, Fowler 1992, E.M. Burbidge 1994, G.R. Burbidge 2007, as have Cameron (1999), Salpeter (2002), Bethe (2003), and Opik (1977), the last addressing many of his innovative ideas in astrophysics but not the triple alpha reaction.…”
Section: Synthesis In Stars -On Beyond Heliummentioning
confidence: 99%
“…The four have told their own versions of the story (Hoyle 1982, Fowler 1992, E.M. Burbidge 1994, G.R. Burbidge 2007, as have Cameron (1999), Salpeter (2002), Bethe (2003), and Opik (1977), the last addressing many of his innovative ideas in astrophysics but not the triple alpha reaction.…”
Section: Synthesis In Stars -On Beyond Heliummentioning
confidence: 99%
“…We do not argue that these simulations are a perfect representation of what one should expect from the integrated light of super-star clusters. Nevertheless, we draw inspiration from Salpeter (2002), who, while musing about the longevity of his 1955 paper, suggested that it is not important for all the assumptions in a calculation be correct, but that the largest uncertainties should tend to cancel!…”
Section: Unresolved Super-star Clustersmentioning
confidence: 99%